2003
DOI: 10.1046/j.0960-7412.2003.001605.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of peroxisomal targeting signal of pumpkin catalase and the binding analysis with PTS1 receptor

Abstract: SummaryMany peroxisomal proteins are imported into peroxisomes via recognition of the peroxisomal targeting signal (PTS1) present at the C-termini by the PTS1 receptor (Pex5p). Catalase, a peroxisomal protein, has PTS1-like motifs around or at the C-terminus. However, it remains unclear whether catalase is imported into peroxisome via the PTS1 system. In this work, we analyzed the PTS of pumpkin catalase (Cat1). A full or truncated pumpkin Cat1 cDNA fused at the 3 0 end of the green fluorescent protein (GFP) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 56 publications
1
37
0
Order By: Relevance
“…The deduced amino-acid sequence of CsCAT3 consists of the conserved catalytic active site and heme-binding site, which play important roles in catalytic function and the heme ligand, suggesting that CsCAT3 is a typical CAT. The subcellular localization prediction of CsCAT3 based on ProtComp, CELLO and Plant-mPLoc indicated that CsCAT3 is targeted to the peroxisome, and the CsCAT3 sequence indicated the presence of a putative peroxisomal targeting signal (PTS1) motif QKIASRMNVRPNI that contains conserved QKL/I/V amino acid residues at the position of 480-482 (Figure 1(B)), which was reported previously [29]. These results clearly demonstrated that CsCAT3 is a peroxisomal catalase, which is consistent with the results of previous studies [18,20,30].…”
Section: Cloning and Characterization Of Cscat3 Genementioning
confidence: 88%
“…The deduced amino-acid sequence of CsCAT3 consists of the conserved catalytic active site and heme-binding site, which play important roles in catalytic function and the heme ligand, suggesting that CsCAT3 is a typical CAT. The subcellular localization prediction of CsCAT3 based on ProtComp, CELLO and Plant-mPLoc indicated that CsCAT3 is targeted to the peroxisome, and the CsCAT3 sequence indicated the presence of a putative peroxisomal targeting signal (PTS1) motif QKIASRMNVRPNI that contains conserved QKL/I/V amino acid residues at the position of 480-482 (Figure 1(B)), which was reported previously [29]. These results clearly demonstrated that CsCAT3 is a peroxisomal catalase, which is consistent with the results of previous studies [18,20,30].…”
Section: Cloning and Characterization Of Cscat3 Genementioning
confidence: 88%
“…Nonperoxisomal targeting of the deletion construct AtAcd31.2DN:EYFP and the version with mutated PTS2 (RLx 5 HF/RLx 5 DF) demonstrated that RLx 5 HF is a functional PTS2 and argued against the presence of an additional internal PTS similar to those described for CAT and a few other proteins (Kamigaki et al, 2003). Subcellular targeting of AtAcd31.2DN:EYFP to plastids was in line with computer prediction for this fusion protein but is not thought to be of physiological significance, because a second putative alternative translational start codon is lacking in front of the predicted transit peptide and because dual targeting of the full-length fusion protein AtAcd31.2:EYFP to both peroxisomes and plastids was not observed.…”
Section: Discussion Experimental Validation Of Peroxisome Targetingmentioning
confidence: 99%
“…35,36 Furthermore, upstream secondary or tertiary structure is also reported to affect import efficiency in plants. 37 Subsequent steps in the PTS1 pathway in vivo could compensate for the loss of efficiency in the recognition and binding step by Pex5p. For example, substitution of the consensus Leu by Ile in PTS1 (SKL to SKI) disrupts peroxisomal localization in other proteins.…”
Section: Discussionmentioning
confidence: 99%